Perilaku Nasabah di Era Digital: Analisis Faktor-Faktor yang Mendorong Penggunaan Electronic Banking (E-Banking) - Idatunnisak, Af; Marhamah, Marhamah; Anwar, Alfian Setia (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This study examines the influence of service knowledge, security assurance, internet connection quality, and transaction capability on customers' interest in using e-banking at PT Bank Rakyat Indonesia (BRI) Tbk, Pekalongan Branch. Despite a significant increase in the number of internet banking users over the past five years, the level of transaction activity using e-banking remains low. The study aims to analyze the factors influencing customers' interest in e-banking, focusing on knowledge, security, connectivity, and ease of transaction. The population consists of BRI Pekalongan Branch customers using e-banking, with a sample of 96 customers selected using accidental sampling. Data analysis includes descriptive statistics, validity and reliability tests, classical assumption tests, and hypothesis testing. The study found that all independent variables significantly influence customer interest, with a significance level of < 0.05. The determination coefficient of 0.871 indicates that these variables explain 87.1% of the variability in customer interest. Service knowledge, security assurance, internet connection quality, and transaction capability are crucial factors in increasing the use of electronic banking among BRI Pekalongan Branch customers. The recommendations for BRI Pekalongan Branch include enhancing e-banking promotion and providing security guarantees to protect customer transaction information.